La détention provisoire au Québec : éléments de connaissance et propositions de réflexions - Cousineau, Marie-Marthe (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1995)
For a long time, it has been argued that pre-trial detention should be used with moderation, only in those occasions where no other means seems sufficient to insure the presence of the suspect at his trial or to warrant the security of the public during the duration of the criminal proceedings. Looking at the official statistics reported by the author, one could easily conclude that, in Canada, the pre-trial detention is still largely used. By following a cohort of 1792 suspects from the moment they were apprehended by the MUC police agents in 1989, till the end of Court procedures, the author identifies the characteristics of the suspects who were maintained in pre-trial detention in comparison to the ones that were not submitted to this measure. Further, the author addresses the controversial question of the consequences of pre-trial detention on penal issues. In conclusion the author raises the question if it could be possible to develop other ways of dealing with what she defines as the perceived risk that a suspect tries escape trial or continues to cause harm to the society during the trial.